Valores hematológicos referenciales de piscitaceos criados en jaula en el trópico seco - Carpio Arias, Lynne Daphne (2012)
The present investigation was whith in the Tumbes city, Perú during months de march and november of the year 2011, with finality of obténvalors reals of the parámetros hematológios species of psitácidascoeatiles (Hollandicus nymphicus), agapornis (Agapornis personatus) y pericosaustralianos (Melopsicatus undulatus). Used to work the following objectives: 1. Stablishe the valorshematológicos in the species Cocatiles (Hollandicus nymphicus), agapornis (Agapornis personatus) y pericos australianos (Melopsicatu sundulatus) in the Tumbes city (Perú) in the year 2011, for the reazon the blood blid of 60 birds, 20 of betwwen species after says, usen methods hematológicos of laboratory be to investigate the following aspects: turn corpuscular medio (VCM), concentrate Hemoglobina corpuscular media (HCM), turn de eritrocitos; turn of leucocitos, Hematocrito, Hemoglobina, turn of hemoglobina corpuscular media (CHM), of plaquetas and the morfology of celules. 2. Yous the differences hematológicas of birds Agapornis, Cockatiles and australiana parrots the agree sex. For investigate and study the valors obtens in the laboratory and comparate to distance the following female and male, for this reason cantstablish the diference of the birds.